National innovation performance: the role of human capital and social capital. Issue 3 (2nd July 2020) - Suseno, Yuliani; Standing, Craig; Kiani-Mavi, Reza; Jackson, Paul
Abstract : Despite the relevance of human capital and social capital as antecedents of innovation, quantitative evidence at the national level is scarce. This study aims to examine the influence of human capital and social capital on national innovation performance, using secondary data of the OECD countries. Our findings indicate that both human capital and social capital have a significant effect on national innovation performance. We also found significant differences between clusters of countries in terms of human capital, social capital, and national innovation performance. The implications of the study contribute to research and practice particularly in policy decision making for business and society.